Targeted in vivo inhibition of specific protein-protein interactions using recombinant antibodies - Zábrady, Matej; Hrdinová, Vendula; Müller, Bruno; Conrad, Udo; Hejátko, Jan; Janda, Lubomír (PloS one, 2014)
With the growing availability of genomic sequence information, there is an increasing need for gene function analysis. Antibody-mediated "silencing" represents an intriguing alternative for the precise inhibition of a particular function of biomolecules. Here, we describe a method for selecting recombinant antibodies with a specific purpose in mind, which is to inhibit intrinsic protein-protein interactions in the cytosol of plant cells. Experimental procedures were designed for conveniently evaluating desired properties of recombinant antibodies in consecutive steps. Our selection method was successfully used to develop a recombinant antibody inhibiting the interaction of ARABIDOPSIS HISTIDINE PHOSPHOTRANSFER PROTEIN 3 with such of its upstream interaction partners as the receiver domain of CYTOKININ INDEPENDENT HISTIDINE KINASE 1. The specific down-regulation of the cytokinin signaling pathway in vivo demonstrates the validity of our approach. This selection method can serve as a prototype for developing unique recombinant antibodies able to interfere with virtually any biomolecule in the living cell.
Keywords: Arabidopsis Proteins; umlčování genů; Gene Silencing; rekombinantní proteiny; Phosphotransferases; Recombinant Proteins; proteinkinasy; Antibodies; signální transdukce; Protein Interaction Maps; Signal Transduction; proteiny huseníčku; mapy interakcí proteinů; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; cytosol; Protein Kinases; Arabidopsis; Cytosol; fosfotransferasy; protilátky